Strategic Management of Multicultural-Based Education (Study at Bakti Karya Vocational High School, Pangandaran) (Educational Management, 2022)
This study aims to see how the right strategy is to manage student diversity in a multicultural-based educational setting. The diversity of multicultural society in Indonesia can be seen as one of the wealth of the nation but is also very prone to trigger conflicts and divisions. The link between education and the diversification of multiculturalism is a solution to diverse cultural realities, so as to minimize conflicts that are initiated by differences. This research uses a descriptive qualitative approach that focused on strategic management activities: planning, implementing, and evaluating strategies. The data collection techniques are gathered through in-depth interviews, observations, and documentation. Finally, the result shows that SMK Bakti Karya has implemented multicultural education well, this can be seen from the process of implementing school strategies that always align with the school’s vision and mission as a school that provides multicultural education. The process of inculcating the values of multiculturalism is always embedded in every learning process so that it is carried out in harmony without discrimination. This shows that the school has a high commitment to carrying out multiculturalism education in accordance with the school’s vision the concept of a public-friendly school.